(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
In the "embedded controller" architecture, a personal computer (PC) is used as a hardware platform for motion control. It allows to plan and control the multi-functional movement of control modules and systems, to perform information and measurement data processing functions in one device.